Generative AI for academics - Carrigan, Mark ca. 20./21. Jh (SAGE, 2025)
This is your indispensable guide to navigating the rise of generative AI as an academic. It thoughtfully explores rapidly evolving AI capabilities reshaping higher education, examining challenges and ethical dilemmas across the sector.It provides useful strategies for using generative AI in your scholarly work while upholding professional standards. This practical guidance addresses four core areas of academic work:- Thinking: How to use generative AI to augment individual and collaborative scholarly thinking that can assist in developing novel ideas and advancing impactful projects- Collaborating: Explore how generative AI can be used as a research assistant, coordinating teams and enhancing scholarly cooperation- Communicating: Cautioning against over-reliance, examine how generative AI can relieve communication burdens while maintaining professionalism and etiquette- Engaging: thoughtful and practical frameworks are offered for using these developments to support online engagement without sacrificing scholarly principlesMark Carrigan is a digital sociologist, author and Lecturer in Education at the University of Manchester
Keywords: Wissenschaftliches Arbeiten; Künstliche Intelligenz; Generative KI; Wissenschaftskommunikation; Wissenschaftliche Kooperation